SISTEM PELAYANAN PENDIDIKAN TERHADAP ANAK PENYANDANG DISABILITAS DI SEKOLAH KHUSUS NEGERI 1 KENDARI - Novri, Rizky; Moita, Sulsalman; Jabar, Aryuni Salpiana (Universitas Halu Oleo, 2022)
The purpose of this study was to examine educational services for children at the Kendari 1 State Special School and to determine the factors supporting and inhibiting educational services for children at the Kendari 1 State Special School. This research uses descriptive qualitative research with data techniques, interviews, and documentation. The results of the study indicate that services for children with disabilities are certainly different from other general children or must be in accordance with the needs of these children where in providing lessons or providing facilities so that they must have a special strategy or program. Supporting factors for children with disabilities in Kendari 1 State Special School are the government, family, teachers and the environment. Meanwhile, the inhibiting factors for children with disabilities in Kendari 1 State Special School are lack of teachers or teaching staff, school entry flows and lack of facilities and infrastructure.